Congenital cavitary optic disc anomaly and Axenfeld's anomaly in Wolf-Hirschhorn syndrome: A case report and review of the literature. (4th March 2018) - Ali, Mohsin H.; Azar, Nathalie F.; Aakalu, Vinay; Chau, Felix Y.; Abbasian, Javaneh; Setabutr, Pete; Maumenee, Irene H.
ABSTRACT: Background : Wolf-Hirschhorn syndrome is a rare genetic syndrome caused by a heterozygous deletion on chromosome 4p16.3 and is characterized by a "Greek warrior helmet" facies, hypotonia, developmental delay, seizures, structural central nervous system defects, intrauterine growth restriction, sketelal anomalies, cardiac defects, abnormal tooth development, and hearing loss. A variety of ocular manifestations may occur in up to 40% of patients. Materials/methods : We report the genetic testing results, systemic findings, and complete ophthalmologic examination findings in a patient with Wolf-Hirschhorn syndrome, including external photography, RetCam3 (Clarity Medical Systems, Pleasonton, CA) goniography, and fundus photography. In addition, we review the literature on ocular manifestations of Wolf-Hirschhorn syndrome. Results : Microarray analysis revealed an unbalanced translocation between 4p16.3–15.3 and Xp22.33-p22.2. Systemic findings included "Greek warrior helmet" facies, hypotonia, cleft palate, neonatal tooth eruption, talipes equinovarus, bilateral clinodactyly, clitoromegaly, partial agenesis of the corpus callosum, bilateral renal hypoplasia, and two atrial septal defects. Ocular findings included normal intraocular pressures and corneal diameters, large-angle exotropia, downward slanting of the palpebral fissures, absent eyelid creases, upper and lower eyelid retraction with shortage of the anterior eyelid lamellae, euryblepharon, lagophthalmos with poor Bell's reflex and exposure keratopathy, hypertelorism, Axenfeld's anomaly, megalopapillae, and cavitary optic disc anomaly. Conclusions : We describe the ocular phenotype of a patient with Wolf-Hirschhorn syndrome, including the rare descriptions and photographs of Axenfeld's anomaly, megalopapilla, and cavitary optic disc anomaly in this condition.